Employees' responses to psychological contract breach: The mediating role of organizational cynicism. (May 2022) - Bari, Muhammad Waseem; Qurrah-tul-ain; Abrar, Muhammad; Fanchen, Meng
This study evaluates employees' responses (turnover intention and counterproductive work behavior) to different forms of psychological contract breach (relational and transactional), and the mediating role of organizational cynicism between employees' responses and psychological contract breach. This study used a time lag technique for data collection from 411 bank employees in Pakistan. PLS-SEM and SmartPls software were applied for data analyses. The findings show that relational psychological contract breach has no significant impact on turnover intention but transactional psychological contract breach has a significant impact on turnover intention. However, counterproductive work behavior has a significant association with both forms of psychological contract breach (relational and transactional). Organizational cynicism significantly mediates the relation of relational psychological contract breach and turnover intention, but fails to mediate the relation between transactional psychological contract breach and turnover intention. Contrary to this, organizational cynicism partially mediates the relation between psychological contract breach (relational and transactional) and counterproductive work behavior. The implications and future directions are discussed in the last section of this study.